1986
DOI: 10.1103/physrevb.34.6041
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic overlayer on Si(111): Removal of surface reconstruction

Abstract: The complex reconstruction characteristic of annealed Si(111) surfaces is removed by the interaction of As with the clean Si(111) 7x7 surface. Surface-sensitive core-level spectroscopy measurements of the Si(111):As 1&1 surface reveal a well-ordered surface with threefoldcoordinated As atoms replacing the Si atoms in the outermost layer. The absence of dangling bonds in this structure leads to an unreconstructed surface which is highly resistant to contamination.Si(~&~) 4s:1x1Side view in the (110) plane of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(56 citation statements)
references
References 11 publications
2
54
0
Order By: Relevance
“…As long as As chemical potential is below the bulk level, the segregated As will evaporate, limiting As adsorption to one monolayer. This is consistent with the experimental observation 5 that excess As can be removed by annealing at a low temperature ͑200°C͒.…”
Section: A Reconstructions Of Si(111)-assupporting
confidence: 93%
See 2 more Smart Citations
“…As long as As chemical potential is below the bulk level, the segregated As will evaporate, limiting As adsorption to one monolayer. This is consistent with the experimental observation 5 that excess As can be removed by annealing at a low temperature ͑200°C͒.…”
Section: A Reconstructions Of Si(111)-assupporting
confidence: 93%
“…The detailed structure is however unclear from the vapor-phase experiments while 1 ϫ 1-As is the only phase found in ultrahigh-vacuum ͑UHV͒ studies. [5][6][7][8][9][10][11] Although previous first-principles calculations have shown that the ͱ 3 ϫ ͱ 3 T 4 adatom, 12-14 ͱ 3 ϫ ͱ 3 trimer, 15 and 2 ϫ 1 zigzag chain 15 FIG. 1.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…, Si(111)6.3 Â 6.3-Ga, [424][425][426][427] Si(111) 1 Â 1-As, [428][429][430] Si(100) 1 Â 1-S, 431,432 and Si(111) 1 Â 1-Cl, 433,434 fabricated in situ, different metals were deposited at cryogenic temperatures and occasionally in an inert gas environment. Since the ATS surfaces were known to be stable to various degrees and the metals were deposited "softly," the expectation was that the surface dipole on the ATS might survive the metal deposition and be available for SBH adjustment.…”
mentioning
confidence: 99%
“…A full microscopic explanation of the surfactant effect is still missing, but several aspects have been clarified: Because of the additional electron, surfactant layers of group-V elements on Si or Ge modify the reconstruction of the surface. For example, the As-covered Si(111) surface shows a ͑1 3 1͒ structure [8] instead of the ͑7 3 7͒ reconstruction of pure Si(111). Group-V atoms have a reduced-surface free energy which makes them float on the surface without being incorporated into the growing crystal [1,9].…”
mentioning
confidence: 99%